(untitled) (Dubuque, 2008)
This Ninth Edition of ANNUAL EDITIONS: WORLD HIST0RY, VOLUME 2, provides convenient, inexpensive access to current articles selected from the best of the public press. Organizational features include: an annotated listing of selected World Wide Web sites; an annotated table of contents; a topic guide; a general introduction; brief overviews for each section; a topical index; and an instructor’s resource guide with testing materials
Keywords: World history,Lịch sử thế giới